Spectrum Distribution in Cognitive Radio: Error Correcting Codes Perspective. (13th July 2014) - Hussain, Syed Azmat; Shah, Tariq; Azam, Naveed Ahmed; Andrade, Antonio Aparecido de; Naveed Malik, Aqdas
Cognitive radio is a growing zone in wireless communication which offers an opening in complete utilization of incompetently used frequency spectrum: deprived of crafting interference for the primary (authorized) user, the secondary user is indorsed to use the frequency band. Though, scheming a model with the least interference produced by the secondary user for primary user is a perplexing job. In this study we proposed a transmission model based on error correcting codes dealing with a countable number of pairs of primary and secondary users. However, we obtain an effective utilization of spectrum by the transmission of the pairs of primary and secondary users' data through the linear codes with different given lengths. Due to the techniques of error correcting codes we developed a number of schemes regarding an appropriate bandwidth distribution in cognitive radio.